Neighborhood-Scale Urban Water Reclamation with Integrated Resource Recovery for Establishing Nexus City in Munich, Germany: Pipe Dream or Reality? - Mohammed S. M. Al-Azzawi; Daphne Gondhalekar; Jörg E. Drewes (Resources, 2022)
With the rapid expansion of cities due to population growth and urbanization, conventional centralized wastewater collection and treatment systems are slowly becoming a burden; expensive maintenance is required for aging plants and piping infrastructure, the cost of expanding the capacity to cover demand from population growth, and new regulations for tighter control over certain pollutants such as micropollutants. As an alternative to this system, this study discusses the feasibility of decentralized treatment systems at the neighborhood scale. Taking a Water-Energy-Food (WEF) Nexus approach, such systems can support water and energy conservation, recovery of water, energy, and nutrients as well as generation of energy from wastewater, be customized to individual water and energy requirements, and eliminate the need for lengthy pipe networks. The method employed in this study is comparing the economic feasibility of the status quo to a proposed decentralized solution. The study finds that the costs of implementing a hypothetical decentralized water reclamation with an integrated resource recovery system using an anaerobic membrane bioreactor (AnMBR) in a downtown high-density neighborhood of the city of Munich, Germany, can theoretically be recuperated within two years. This alternative system may cost 60% of what it costs to run the centralized system. By linking the AnMBR to a biogas digestor and using systematically harvested organic waste as a co-substrate, the decentralized system can generate enough energy to run itself and even feed some energy to the grid. This study is highly hypothetical, yet generating evidence such as this can support a systemic socio-technical transition towards a more circular economy with optimal resource recovery.